2019
DOI: 10.1103/physrevb.100.104418
|View full text |Cite
|
Sign up to set email alerts
|

Numerical observation of a glassy phase in the three-dimensional Coulomb glass

Abstract: The existence of an equilibrium glassy phase for charges in a disordered potential with long-range electrostatic interactions has remained controversial for many years. Here we conduct an extensive numerical study of the disordertemperature phase diagram of the three-dimensional Coulomb glass model using population annealing Monte Carlo to thermalize the system down to extremely low temperatures. Our results strongly suggest that, in addition to a charge order phase, a transition to a glassy phase can be obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
(133 reference statements)
2
10
0
Order By: Relevance
“…Analytic studies have demonstrated mean-field similarity to the SK spin glass and predicted a sharp phase transition to a spin-glass like phase above a critical disorder [38,37]. A recent computer simulation of this case [39] using modern sophisticated scaling tests has demonstrated a sharp transition from plasma/paramagnet to a Coulomb Glass state as temperature is reduced, beyond a sufficient strength of quenched randomness .…”
Section: Coulomb Glassmentioning
confidence: 91%
“…Analytic studies have demonstrated mean-field similarity to the SK spin glass and predicted a sharp phase transition to a spin-glass like phase above a critical disorder [38,37]. A recent computer simulation of this case [39] using modern sophisticated scaling tests has demonstrated a sharp transition from plasma/paramagnet to a Coulomb Glass state as temperature is reduced, beyond a sufficient strength of quenched randomness .…”
Section: Coulomb Glassmentioning
confidence: 91%
“…So like RFIM system there exist two fixed points (W = 0, T = T c ) and (W = W c , T = 0). Both the work on CG model [5,6] shows that the critical exponents for W < W c are similar to the ones at zero temperature fixed point as seen also in RFIM [7][8][9][10]. So it was concluded that at least at small disorders, both CG and RFIM belong to the same universality class One should note that in both these works, the on-site energies are modeled by a Gaussian distribution.…”
Section: Introductionmentioning
confidence: 79%
“…The phase diagram of the three-dimensional CG model [5,6,11] is quite well established now, suggesting a Charge Ordered (CO) phase below a particular value of disorder (W c ). Since the ground state is antiferromagnetic at zero and small disorders, therefore, the staggered magnetization, M s (which is the difference between two sublattice magnetizations) is the appropriate order parameter here.…”
Section: A Staggered Magnetizationmentioning
confidence: 99%
See 2 more Smart Citations